Wujud Pragmatik Imperatif Dalam Buku Ajar Bahasa Indonesia 2 SMA Kelas XI Karangan Sri Sutarni Dan Sukardi - Indarti, Indarti, Dra. Atiqa Sabardila, M. Hum (2016)
FARM OF IMPERATIVE IN BAHASA INDONESIA 2 SMA YEAR XI BOOK COMPOSITED BY SRI SUTARNI AND SUKARDI. Skripsi thesis. Faculty of Teacher Training and Education,Muhammadiyah University of Surakarta. June, 2016. When the sentence is clear and understandable, the meaning can influence the reader. One of the sentence's meanings is commanding. The aim of imperative santence Is that the speaker wants the hearer to do something as ordered or commanded by utterences. The written imperative sentence can be marked by using the imperative mark. The spoken imperative sentence can be known by unadorned and loud sound from the speaker. Imperative sentence can be divided into some kinds, so in the studying we can know not only the forms but also the shapes. The aims of this study are (1) to show the imperative classification of pragmatic forms in teaching Bahasa Indonesia 2 SMA year XI book composited by Sri Sutarni and Sukardi. (2) to describe the pragmatic forms of imperative inteaching Bahasa Indonesia 2 SMA year XI book composited bY Sri Sutarni and Sukardi. This study is qualitative study. The data of this study are the utterances that have imperative meaning. The data source is Bahasa Indonesia 2 SMA year XI book composited by Sri Sutarni and Sukardi. Documentation is the data collection technique in this study with note taking. The data analyzing technique are data reduction and data analyze. The results of this study show that two. They are (1) five forms of imperrative in Bahasa Indonesia 2 SMA year XI book composited by Sri Sutarni and Sukardi. They are: (a) utterances that have illocutionary acts of order, (b) command, (c) wish, (d) appeal, and (e) request. The researcher also found two kinds of imperrative sentence based on the action that have imperrative meaning. They are: (a) the imperrative sentence using suffix -lah, and (b) the refined imperrative sentences. The common imperratives using suffix -lah are divided sentences using transitive and intransitive verb. The refined imperrative sentences can be divided into 3 kinds of using, they are (a) using compliment, (b) using connunction, and (c) using prefix.(2) Identification of (a) suffix -lah and (b) using sentence.